Upaya Pemerintah Mengurangi Kemiskinan Melalui Program BSPS Di Kabupaten Ponorogo - Ramadhania, Faiza Eka; Taufiq, M.; Wijaya, Riko Setya (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to find out how the government's efforts to reduce poverty through the BSPS program in Ponorogo Regency. All methods have been implemented by the government, one of which is through the Self-Help Housing Stimulant Assistance (BSPS) program. The purpose of this study is to analyze the level of community welfare and analyze the depletion of the poverty rate in Ponorogo Regency. The methods used to collect data include direct observation, interviews with informants, literature studies and documentation. While the method used in analyzing the data is descriptive analysis starting from data collection, data processing, data presentation and drawing conclusions. The results of this study concluded that the Self-Help Housing Stimulant Assistance (BSPS) program had not significantly provided a way out in reducing poverty in Ponorogo Regency